Inflammatory myopathies in a patient with Darier\'s disease, a possible association - Kaveh Gharaeinejad; Hojat Eftekhari; rana rafiei; Abbas Darjani; Narges Alizadeh (Babol University of Medical Sciences, 2018)
Background: Darier disease (DD) is an autosomal dominant genetic disorder which develops from a mutation in the ATP2A2 gene. Inflammatory myopathies (IM) are the largest group of potentially treatable myopathies. In this case, we report development of IM in a patient with DD for the second time in the literature. Case presentation: The patient is a 59-year-old female, a known case of  DD, who developed proximal muscle weakness 2 weeks prior to admission. Elevated muscle-enzymes, as well as typical electromyographic and radiologic confirmed the diagnosis of IM. Conclusions: Abnormalities in intracellular calcium homeostasis may explain the association between DM and DD, therefore it is noteworthy to keep this association in mind and conduct more research regarding this issue